Chapter Careening areas in marinas, anchorages, and private shipyards. Status of implementation of the MSFD measure - Droit, Julie (Proceedings e report, 2020)
Ship careening, which consists of stripping antifouling paint, generates waste. These residues contain different chemical contaminants that can have an impact on the marine environment. The implementation of the Marine Environment Strategy Framework Directive has been declined through the adoption of Action Plans. Cerema was mandated by the Ministry of Ecology to carry out a national study identifying the level of equipment in fairing areas of marinas, anchorages and private shipyards. The data collected are available on the Geolittoral site: www.geolittoral.developpement-durable.gouv.fr